2022
DOI: 10.52449/1857-4114.2020.38-2.09
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Physical Education in the Well-Being and School Performance of Pupils

Abstract: Abstract. The ever-changing ideals of modern society often tend to set too bold goals based on theoretical knowledge that can lead to great results. All these can have negative influences on mental health, characterized by a high degree of stress, exaggerated emotional reactions, reduced cognitive activity, inappropriate behaviors in the educational and social environment. Under these conditions, the practice of physical activities can be the optimal alternative for primary school pupils in order to eliminate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Physical activity is a fundamental premise for the mental health of young students, as it contributes to reducing tension and stress [ 23 , 24 ]. Various studies have shown that psychological distress, depression, and anxiety disorders negatively correlate with engagement in moderate physical activities [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Physical activity is a fundamental premise for the mental health of young students, as it contributes to reducing tension and stress [ 23 , 24 ]. Various studies have shown that psychological distress, depression, and anxiety disorders negatively correlate with engagement in moderate physical activities [ 25 ].…”
Section: Introductionmentioning
confidence: 99%